MANAGEMENT OF CULINARY BUSINESS KOPI BUKAN LUWAK PAKEM, SLEMAN, YOGYAKARTA AS A CREATIVE INDUSTRY - Suwandojo, Dodik Prakoso Eko Hery; Wati, Ika Wahyu Kusuma (Prosiding Pendidikan Teknik Boga Busana, 2021)
The culinary business in Yogyakarta is growing rapidly. Culinary development is in line with the development of culture and customer behavior. Culinary is one of the priority sectors for Yogyakarta because it is closely related to tourism which functions as a tourist attraction. Culinary and tourism both complement each other as a convenience. Yogyakarta with its trademark has many varieties and types of culinary, one of which is a coffee shop. Kopi Bukan Luwak is a warong or coffee shop located in the Pakem area, Sleman, Yogyakarta where in this area there are many similar coffee shop businesses, both in terms of the menu served, similar in terms of service and in terms of atmosphere, and scenery. But uniquely this coffee shop is never empty of customers. In connection with this phenomenon, it is necessary to know how to manage this coffee shop in order to survive in the midst of competition but still attract customers. By using qualitative descriptive methods and direct data collection in the field, this research is expected to reveal how to manage the culinary business of this coffee shop. Management by involving stakeholders in several parts of the culinary business provides opportunities for positive interactions to win the competition and build customer intimacy. Keywords: Management, Culinary, Loyalty, Customer.